INNOVATING THE MICE INDUSTRY THROUGH CREATIVE TOURISM: OPPORTUNITIES AND FUTURE DIRECTIONS - Disimulacion, Maria Arlene Fernali (Politeknik Pariwisata NHI Bandung, 2024)
Creative tourism and Meetings, Incentives, Conventions, and Exhibitions (MICE) tourism are two independent sectors positioned for distinct markets, namely, the leisure and the business groups. However, the sweeping shifts in tourist motivation, behavior, and interest toward immersive, engaging, and sustainable activities may require an innovative strategy that can mutually benefit stakeholders across the value and supply chain. Thus, this paper seeks to present the possibility of a niche for both types of tourists. Anchored on grounded theory, the research argues for inclusion of unique activities curated by residents for a MICE itinerary. However, the strategy requires best new practices in the conceptualization, management, and evaluation of this new offer that will achieve profit objectives, ensure the well-being of the residents, safeguard traditions, and protect the communities, thus, resulting in a sustainable and regenerative tourism ecosystem.